Centro comercial como recinto de vida urbana; tipología para reubicación de vendedores informales - Sánchez Vargas, Natalia (Universidad Antonio Nariño, 2022)
The research project proposes a commercial infrastructure focused on the relocation of informal vendors in Neiva-Huila based on the reinterpretation of the traditional typology of the mall and its building-environment relationship. Under an evolutionary contemporary documentary study, an analog analysis was made of the background of shopping malls in Colombia that were built for the relocation of informal vendors, as well as an analysis of contemporary shopping centers in order to highlight the problems of the traditional shopping center and the advances in the typology of the shopping center today. Likewise, through a field study, primary data were obtained under the structured survey mechanism in order to understand the profile of the population under study.